Understanding Political Scandals Using a Social Representations Approach: The Case of the Philippine Priority Development Assistance Fund Scam - Baquiano, Marshaley J. (Silliman Journal, 2022)
The study puts forward the use of Social Representations Theory in investigating Filipinos’ shared understanding of the scandal surrounding the Philippine legislators’ Priority Development Assistance Fund. Employing the word association technique, 151 Filipinos who were familiar with the event wrote down the social meanings they associated with the fund scam. Data were analyzed using thematic analysis and hierarchical evocation method (Abric, 2012). Respondents’ core understanding of the scam depicted the issue as a story of corruption, which was orchestrated by Janet Lim-Napoles. On the other hand, the respondents’ peripheral apprehension centered on depicting the scandal as one that involved the government and some corrupt legislators. Hence, the pork barrel scam was viewed as a form of injustice that pointed to the greed and insincerity of the legislators involved, and the kind of system the Philippine government had. Because of the scandal, Filipinos had felt enraged and betrayed, and were then calling for genuine change in the system. Moreover, the pork barrel scam was largely associated with Lim-Napoles, and the implicated legislators were likened to baboy (swine). In sum, findings point to the potency of the Social Representations Theory in investigating political scandals, such as the pork barrel scam.